2015
DOI: 10.3177/jnsv.61.201
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Androgenic Activity of Icarisid II from Epimedium Herb in Prostate Cancer LNCaP Cells

Abstract: Summary Anti-androgens are regarded as potential therapeutic agents for the treatment of prostate cancer. We determined that an epimedium herb (EH) extract exhibited antiandrogenic activity in a luciferase assay using androgen receptor-positive prostate cancer LNCaP cells. Nine EH-derived flavonoids were examined. The results identified icarisid II as a very potent anti-androgenic EH-derived flavonoid. A quantitative RT-PCR analysis confirmed that the flavonol suppressed the expression of the androgen-responsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In an in vivo study, reduction of tumor growth was seen in murine models implanted with androgen-sensitive and CRPC cells, due to inhibition of AR signaling by icaritin (Sun et al, 2015a ). In another study, the treatment of androgen receptor-positive prostate cancer cells with icariside II resulted in downregulation of expression of KLK3 gene, showing the role of icariside II in inhibition of AR signaling (Miura et al, 2015 ).…”
Section: Anticancer Propertiesmentioning
confidence: 99%
“…In an in vivo study, reduction of tumor growth was seen in murine models implanted with androgen-sensitive and CRPC cells, due to inhibition of AR signaling by icaritin (Sun et al, 2015a ). In another study, the treatment of androgen receptor-positive prostate cancer cells with icariside II resulted in downregulation of expression of KLK3 gene, showing the role of icariside II in inhibition of AR signaling (Miura et al, 2015 ).…”
Section: Anticancer Propertiesmentioning
confidence: 99%
“…Likewise, rutin, another flavonol glycoside isolated from Solanum macaonense releaved to have selective moderate cytotoxicity toward DU145 cancer cell lines (IC 50 = 31.8 ÎŒM) [241]. A flavonoid glycoside from Epimedium herb extract, icarisid II, indicated a very potent antiproliferative effect on LNCaP cells at 10 ”M with less than 25% of cell viability and suppressed the expression of the androgen-responsive KLK3 gene [220].…”
Section: Plant Extracts and Plant-derived Bioactives In Prostate Cmentioning
confidence: 99%
“…Importantly, recent studies also suggested that non-androgens including various growth factors, cytokines, protein kinases or interacting with selective coactivators could also transactivate AR in an androgen-independent mechanism [ 11 ]. Targeting AR, instead of targeting the androgens with antiandrogens, to better suppress the AR-mediated CRPC progression is urgently needed [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%